CRANIOMETRIC COMPARISONS OF THE SKULL OF MALE AND FEMALE MALAKLI DOGS USING 3-DIMENSIONAL IMAGING: A COMPUTED TOMOGRAPHY (CT) STUDY - Guzel, B. C.; Baygeldi, B.; Demircioglu, I.; Ilguen, R.; Ozkan, Z. E. (Pakistan Agricultural Scientists Forum, 2023)
The skull is an important anatomical structure to discern dog breeds and wolves from dogs. For this purpose, skull morphology and some morphometric measurements of Malakli dogs, a local breed in the Aksaray region, were examined. Thirty-one distances were measured, and the skulls, which were computerized tomography, were converted into three-dimensional (3D) images in fourteen skulls (7 male-7 and female) of adult dogs. Different morphological features and statistical findings that were not revealed by taking measurements from 30 distinct anatomical points of Aksaray Malakli dog skull bones were determined in accordance with the literature. It was determined that males were greatest than females in most of the osteometric measurements as well as in surface area and volume measurements. Through examination of the cranial morphometric characteristics and 3D images of Aksaray Malakli dogs, the results of this study demonstrated differences between the sexes. In addition to showing some similarities to the cranial structure of several carnivores, there are also some different anatomic characteristics.
Keywords: 3D modeling; Computed tomography; Craniometric; Malakli dog